2016
DOI: 10.1007/s40520-016-0549-y
|View full text |Cite
|
Sign up to set email alerts
|

A correlational study between signature, writing abilities and decision-making capacity among people with initial cognitive impairment

Abstract: The analysis of spontaneous writing can be a reliable aid in cases of retrospective evaluation of cognitive integrity. On the other side, the ability to sign is not an index of cognitive integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Authors conclude the work stating that dementia has residual impact on signature formation. A similar finding is reported by Reiner et al [82] which acquired two samples of signature and a spontaneous writing from 36 persons with Mild Cognitive Impairment (MCI) diagnosis and 38 HC. Cognitive functions in decisionmaking were also evaluated: while a significant correlation between spontaneous writing and neuropsychological test results was observed, signature deterioration did not appear to be correlated with the level of cognitive decline.…”
Section: Handwritten Taskssupporting
confidence: 86%
“…Authors conclude the work stating that dementia has residual impact on signature formation. A similar finding is reported by Reiner et al [82] which acquired two samples of signature and a spontaneous writing from 36 persons with Mild Cognitive Impairment (MCI) diagnosis and 38 HC. Cognitive functions in decisionmaking were also evaluated: while a significant correlation between spontaneous writing and neuropsychological test results was observed, signature deterioration did not appear to be correlated with the level of cognitive decline.…”
Section: Handwritten Taskssupporting
confidence: 86%
“…The best classification performance was obtained by using a Bagging CART (classification and regression tree) classifier. It is worth noting that some contrasting result was obtained by Renier et al [103], who found no significant correlation between signature deterioration and level of cognitive decline.…”
Section: Disease Diagnosismentioning
confidence: 77%
“…He observed that the patient reduplicated the same syllable and forgot some others. Recently, several studies have analyzed the writing process dynamics to identify and monitor AD, revealing that writing, persevering, substitution, misalignments of strokes, link and spacing errors indicate a deterioration of fine motor skills and of coordination [36][37][38] .…”
Section: Alzheimer's Disease and Mild Cognitive Impairmentsmentioning
confidence: 99%
“…Moderate AD subjects differ from mild subjects and controls for all written and verbal tasks; Grapho-motor impairments come in addition to the lexical and phonological impairments. 3 [37] ; [38] .…”
Section: Alzheimer's Disease and Mild Cognitive Impairmentsmentioning
confidence: 99%